2016
DOI: 10.1016/j.jjcc.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modern risk scores in predicting operative mortality for patients undergoing aortic valve replacement for aortic stenosis

Abstract: The EuroSCORE II and the Japan score showed superior ability of calibration, but the STS score and the Ambler score overestimated the risk. However, the discrimination power was similar among the four risk scores. In the last quartile of risk, the EuroSCORE II gave an excellent predictive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…This has also been suggested in other previous published studies. For example, the work by Yamaoka and colleagues suggested that STS scores may overestimate the true mortality risk of TAVR [ 11 ]. On the other hand, a meta-analysis from 2014 suggested that both of these scoring algorithms underestimate the risk of TAVR [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has also been suggested in other previous published studies. For example, the work by Yamaoka and colleagues suggested that STS scores may overestimate the true mortality risk of TAVR [ 11 ]. On the other hand, a meta-analysis from 2014 suggested that both of these scoring algorithms underestimate the risk of TAVR [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively studied consecutive patients with symptomatic severe native tricuspid aortic valve stenosis treated with TAVI in a tertiary hospital between May 2008 and May 2014. After evaluation by the dedicated heart team of our hospital, consisting of interventional cardiologist, non-invasive cardiologist anesthesiologists, and two cardiac surgeons, patients who were diagnosed with severe aortic stenosis were considered for TAVI, if the logistic EuroSCORE was !20 risk for surgical replacement or if they were considered ''inoperable'' as previously described [4][5][6]. After the decision was made for appropriateness of TAVI, patients were assigned to one of the two interventional cardiologists.…”
Section: Study Populationmentioning
confidence: 99%
“…The Japan score was developed to establish an original Japanese risk predictive model [ 5 ]. Yamaoka et al compared the predictive value of operative mortality between EuroSCORE II, STS score and Japan score in patients undergoing AVR for AS [ 6 ]. Operative mortality was 3.4%, while the EuroSCORE II, STS score and Japan score were 3.1, 4.9 and 3.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%